Determinants of top commercial banks profitability in selected ASEAN country: panel analysis / Ervisster Tony - Tony, Ervisster (2017)
This paper intend to investigate the relationship between the determinants of profitability in selected top commercial bank in selected ASEAN country that are DBS Bank from Singapore, Maybank from Malaysia, Bangkok Bank from Thailand, Bank Mandiri from Indonesia, and Bank of Philippine Islands from Philippines. Panel analysis are employed to analyse the model regression during the time line from 2007 until 2015 and 5 top commercial banks in each selected ASEAN as the sample. ROA was chosen as the proxy to estimate the top commercial bank’s profit, and 3 independent variables are chosen which size of bank as the bank-internal determinant and gross domestic product growth and inflation rate as the macroeconomic elements. After running these data on the data analysis software using STATA12, it is found that all variables are positive relationship and the major determinants of bank’s profit are inflation rate since it has the most significant value. As the inflation within the country continue to arise, banks able to adjust their interest rate in order to cope with the inflationary environment and gain some profits.